Energy consumption and qualitative evaluation of a continuous band microwave dryer for rice paddy drying. (1st January 2018) - Jafari, Hassan; Kalantari, Davood; Azadbakht, Mohsen
Abstract: In this study, a laboratory scale continuous-band microwave dryer was fabricated and used for drying the paddy. The experiments were carried out at 3 microwave powers (90, 270, and 450 W), conveyor speed 0.24 m/min, and 3 paddy layer thicknesses (6, 12, and 18 mm). The penetration depth of the waves into the examined paddy was obtained equal to 12.7 mm at 25.46% moisture content (w.b %). The maximum energy absorption (81.46%) was obtained at 90 W power and 18 mm layer, whereas the minimum energy absorption was obtained equal to 34.90% at 6 mm paddy thickness and 270 W microwave power. The obtained results indicated that the maximum energy efficiency, the maximum thermal efficiency, the maximum drying efficiency, the minimum specific energy consumption, and the minimum seed breakage percent occurred at 90 W microwave power and 18 mm drying thickness. Therefore as a final concluding result, drying thickness of 18 mm and microwave power of 90 W was selected as the most appropriate combination for drying paddy using the continuous band microwave dryer. Highlights: The maximum energy absorption was obtained at 90 W power and 18 mm layer. The minimum energy absorption was obtained at 6 mm paddy thickness and 270 W. The penetration depth of the waves into the examined paddy was obtained equal to 12.7 mm. The maximum thermal efficiency, maximum drying efficiency were observed at 90 W power. The minimum specific energy consumption, and seed breakage percentage were observed at 90 W power.